Survey on Privacy Preservation in Big Data for Healthcare Monitoring - Anirudh K, Mangore; M Roberts Masillamani, Dr. (International Journal of Engineering and Technology, 2018)
This paper represents the prototype ofÂ  health monitoring system using Big Data. this brings several AdvantageÂ  to the healthcare industry by way of providing timely patient care services, proactive disease detection, real-time monitoring among others. The major challenge faced by healthcare providers on safeguarding the confidentiality of patientsâ€™ data.if confidentiality is not well maintained, people may be unable to share their data. Because security has been investigated as a new dimension, â€œveracity,â€ in big data, we aim to exploit new challenges of big data in terms of security and devote our attention toward efficient and privacy-preserving computing in the big data era. Specifically, we primary formalize the basic architecture of big data analytics, identify the corresponding privacy requirements, and introduce an efficient and privacy Triple DES as an example in response to data miningâ€™s efficiency and privacy requirements in the big data era. The results of this research exhibit that the proposed system has better secured database access and maintain privacy for all patient data than the traditional database.Â
Keywords: Big Data; Cryptography; Cloud Computing; Privacy; Triple DES